Long-term follow-up study and long-term care of childhood cancer survivors - Hyeon Jin Park (Korean Journal of Pediatrics, 2010)
The number of long-term survivors is increasing in the western countries due to remarkable improvements in the treatment of childhood cancer. The long-term complications of childhood cancer survivors in these countries were brought to light by the childhood cancer survivor studies. In Korea, the 5-year survival rate of childhood cancer patients is approaching 70%; therefore, it is extremely important to undertake similar long-term follow-up studies and comprehensive long-term care for our population. On the basis of the experiences of childhood cancer survivorship care of the western countries and the current Korean status of childhood cancer survivors, long-term follow-up study and long-term care systems need to be established in Korea in the near future. This system might contribute to the improvement of the quality of life of childhood cancer survivors through effective intervention strategies.